(untitled) (Scientiae Studia, 2014)
Over the last decades, in biology there has been a proliferation of subdisciplines and theories, and this poses a question about its unity. Consequently, after reductionism was abandoned as a unifying strategy, philosophical questions have been raised about the possibility of alternative forms of relations among the subdisciplines, and whether they can effectively accomplish a unity of biology. This article starts with a brief consideration of some of the problems that the reductionist program confronts in biology, and then analyzes different kind of relations that are present among the subdisciplines of contemporary biology. In particular, we investigate four of the main proposals that can be found in the specialized philosophical literature; and then we propose two models of inter-disciplinary relations: isomorphism in evolutionary biology, and import/export of theoretical corpus, present in the relation between ecology and physiology. Finally, we offer a few ideas on unity as a goal for science in general, and also about the kind of cohesion that we think to be possible for biology based on our analysis. Thus, we defend the idea of pluralism of inter-disciplinary relations and of unity as a local phenomenon.